Odpowiedzi

2010-03-02T21:36:10+01:00
Rozłóż wielomian na czynniki (proszę z obliczeniem a nie sam wynik)
-6x^4+8x³-3x²+4x

-6x⁴+ 8x³ - 3x² + 4x =
-6x⁴ -3x² + 8x³ + 4x =
-3x²(2x² +1) + 4x( 2x² + 1) =
( -3x² + 4x)(2x² +1) =
-x( 3x + 4) (2x² + 1)
1 5 1
  • Użytkownik Zadane
2010-03-02T21:36:50+01:00
-6x^4+8x³-3x²+4x = -2x^3(3x-4)-x(3x-4)=(3x-4)(-2x3-x)=-x(3x-4)(2x+1)
x=0 v x=4/3 v x=1/2
1 5 1
Najlepsza Odpowiedź!
2010-03-02T21:38:31+01:00
-6x^4+8x³-3x²+4x=
(6x^4+3x²) + (8x³+4x)=
-3x²(2x²+1)+4x(2x²+1)=
(2x²+1) (-3x²+4x)=
(2x²+1) -x(3x-4)
1 5 1